2007
DOI: 10.1016/j.ccr.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nucleosomal Occupancy in the Epigenetic Silencing of the MLH1 CpG Island

Abstract: Epigenetic silencing of tumor suppressor genes is generally thought to involve DNA cytosine methylation, covalent modifications of histones, and chromatin compaction. Here, we show that silencing of the three transcription start sites in the bidirectional MLH1 promoter CpG island in cancer cells involves distinct changes in nucleosomal occupancy. Three nucleosomes, almost completely absent from the start sites in normal cells, are present on the methylated and silenced promoter, suggesting that epigenetic sile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 196 publications
(175 citation statements)
references
References 45 publications
10
163
0
2
Order By: Relevance
“…The other three genes, miR-137, miR-193a and miR-127, were expressed even in cell lines with complete methylation, and were unlikely to be silenced by promoter methylation in gastric cancers. Since methylation of putative promoter regions consistently represses transcription of their downstream genes, 29,30 the presence of the expression of the three genes in gastric cancer cell lines with complete methylation of their ''promoter'' CGI indicated that the three genes had additional or alternative promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three genes, miR-137, miR-193a and miR-127, were expressed even in cell lines with complete methylation, and were unlikely to be silenced by promoter methylation in gastric cancers. Since methylation of putative promoter regions consistently represses transcription of their downstream genes, 29,30 the presence of the expression of the three genes in gastric cancer cell lines with complete methylation of their ''promoter'' CGI indicated that the three genes had additional or alternative promoters.…”
Section: Discussionmentioning
confidence: 99%
“…1a), whose methylation statuses are now known to be critical for induction of gene silencing. 29,30 qMSP was performed by real-time PCR using SYBR 1 Green I (BioWhittaker Molecular Applications, Rockland, ME) and an iCycler Thermal Cycler (Bio-Rad Laboratories, Hercules, CA). Although the same primer set was used for qMSP, a specific annealing temperature in the presence of SYBR 1 Green I was redetermined using the fully methylated and unmethylated DNA.…”
Section: Cell Lines and Tissue Samplesmentioning
confidence: 99%
“…4B, middle). MLH1 is a target gene activated by p53, but it is unmethylated (25,35), and its expression is not significantly affected by 5aza-dC treatment of HCT116 cells (microarray signals: HCT116 and HCT116 ϩ 5aza-dC, 189 and 152 arbitrary units, respectively).…”
Section: Nek2 Repression By Exogenously Expressed P53mentioning
confidence: 99%
“…Both doxo and 5aza-dC have been shown to alter chromatin structure, including causing eviction or turnover of nucleosomes (35,38). To determine whether drug treatment causes changes in nucleosome occupancy at the NEK2 promoter, nuclei from HCT116 cells treated with or without 5aza-dC or doxo were digested with MNase and analyzed by qPCR using convergent primers spanning the p53-binding region (Fig.…”
Section: Modulation Of P53 or Treatment With 5aza-dc Leads To Local Cmentioning
confidence: 99%
“…10,[15][16][17] These studies implicated several factors in the propensity of given CpG sites to remethylate, including proximity to a transcription start site (TSS), occupancy of RNA Polymerase II (RNAP II), and the presence of certain histone modifications. 10,16 Given the widespread use of these agents and the promising clinical trials underway utilizing DAC or related compounds as a synergistic or sensitizing agents, [4][5][6] it is vital to understand both the extent and stability of DACinduced demethylation given its immediate potential to improve cancer treatment.…”
Section: Introductionmentioning
confidence: 99%